Experimental investigation of convex tubular solar still performance using wick and nanocomposites. (October 2021) - Essa, F.A.; Alawee, Wissam H.; Mohammed, Suha A.; Dhahad, Hayder A.; Abdullah, A.S.; Omara, Z.M.
Abstract: In this work, the performance of tubular solar still (TSS) was aimed to be improved experimentally. Increasing the surface area inside the solar still is a main parameter of its performance. So, a new-designed convex absorber was used for the first time instead of the flat plate absorber to increase the vaporization and exposure surface areas inside the solar still. The TSS with a convex absorber was nominated as convex tubular solar still (CVTSS). In addition, for further improvement of CVTSS performance, two different types of wick materials (jute cloth and cotton wick) were investigated. Moreover, the effect of using TiO2 and graphene nanocomposites on the CVTSS performance was studied. Experimental results obtained that using the convex absorber increased the vaporization surface area by around 21.3%. So, the water distillate of the CVTSS was greater than that of the TSS under all investigated conditions. Besides, using the jute cloth with the CVTSS improved the daily distillate by 114% and 92.5% with and without nanocomposites, respectively. The highest daily productivity of CVTSS was obtained when using jute cloth with nanocomposites, where it was 9000 mL/m 2 .day versus 4200 mL/m 2 .day for TSS. Additionally, the average daily thermal efficiency of TSS and CVTSS with jute cloth and nanocomposites was 33% and 50%, respectively. Finally, the proposed design is helpful in enhancing the performance of solar still without any extra horizontal spaces or components.